Career and Family Decisions: Cohorts Born 1935-1975 - Eckstein, Zvi; Keane, Michael; Lifshitz, Osnat (Econometrica, 2019)
Comparing the 1935 and 1975 U.S. birth cohorts, wages of married women grew twice as fast as for married men, and the wage gap between married and single women turned from negative to positive. The employment rate of married women also increased sharply, while that of other groups remained quite stable. To better understand these diverse patterns, we develop a life-cycle model incorporating individual and household decisions about education, employment, marriage/divorce, and fertility. The model provides an excellent fit to wage and employment patterns, along with changes in education, marriage/divorce rates, and fertility. We assume fixed preferences, but allow for four exogenously changing factors: (i) mother's education, health, and taxes/transfers; (ii) marriage market opportunities and divorce costs; (iii) the wage structure and job offers; (iv) contraception technology. We quantify how each factor contributed to changes across cohorts. We find that factor (iii) was the most important force driving the increase in relative wages of married women, but that all four factors are important for explaining the many socio-economic changes that occurred in the past 50 years. Finally, we use the model to simulate a shift from joint to individual taxation. In a revenue-neutral simulation, we predict this would increase employment of married women by 9% and the marriage rate by 8.1%.